2021
DOI: 10.3389/fmicb.2021.608839
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of C⋅C Mismatches in DNA by the Escherichia coli Fpg Protein

Abstract: DNA polymerase III mis-insertion may, where not corrected by its 3′→ 5′ exonuclease or the mismatch repair (MMR) function, result in all possible non-cognate base pairs in DNA generating base substitutions. The most thermodynamically unstable base pair, the cytosine (C)⋅C mismatch, destabilizes adjacent base pairs, is resistant to correction by MMR in Escherichia coli, and its repair mechanism remains elusive. We present here in vitro evidence that C⋅C mismatch can be processed by base excision repair initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Unfortunately, no precise data concerning, for example, electron transfer chain is available (Popov et al, 2020). However, there are evidences showing only β-elimination products of FPG activity and both β,δ-elimination products of OGG1 action (Yin et al, 2015;Tesfahun et al, 2021), which were also observed in this study. The explanation may be that due to the liability of the AP-site, the mechanism of its degradation differs depending on the reaction conditions.…”
Section: Introductionsupporting
confidence: 61%
“…Unfortunately, no precise data concerning, for example, electron transfer chain is available (Popov et al, 2020). However, there are evidences showing only β-elimination products of FPG activity and both β,δ-elimination products of OGG1 action (Yin et al, 2015;Tesfahun et al, 2021), which were also observed in this study. The explanation may be that due to the liability of the AP-site, the mechanism of its degradation differs depending on the reaction conditions.…”
Section: Introductionsupporting
confidence: 61%